2012
DOI: 10.5664/jcsm.1766
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Involvement in CPAP: Does Pressure Help?

Abstract: Study Objectives: Continuous positive airway pressure (CPAP) improves sleep and quality of life for both patients with obstructive sleep apnea (OSA) and their spouses. However, few studies have investigated spousal involvement in treatment adherence. Aims of this observational study were to assess perceptions of spousal involvement and evaluate associations between involvement and adherence. Methods: Spousal involvement in CPAP adherence was assessed in 23 married male OSA patients after the fi rst week of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
1
33
1
1
Order By: Relevance
“…[17][18][19] Certain factors have already been associated with poor adherence to CPAP therapy: lack of sleep specialist consultation prior to polysomnogram (PSG), 20,21 African American race, 20,22 low socioeconomic status, [23][24][25] reduced nasal airway caliber, 26 and mask leak, 27 to name a few. Social factors, such as living with another person, 28 spousal involvement, 29 and participation in educational support groups 30 are associated with improved CPAP adherence. Other factors, including OSA severity, body tionnaires [33][34][35][36] and serial assessments, 37 which are useful in a research model but may not be practical in a clinical setting.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…[17][18][19] Certain factors have already been associated with poor adherence to CPAP therapy: lack of sleep specialist consultation prior to polysomnogram (PSG), 20,21 African American race, 20,22 low socioeconomic status, [23][24][25] reduced nasal airway caliber, 26 and mask leak, 27 to name a few. Social factors, such as living with another person, 28 spousal involvement, 29 and participation in educational support groups 30 are associated with improved CPAP adherence. Other factors, including OSA severity, body tionnaires [33][34][35][36] and serial assessments, 37 which are useful in a research model but may not be practical in a clinical setting.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…A closer assessment of spousal involvement (i.e., collaborative, one-sided, positive, and negative) during the first 3 mo of CPAP treatment in 23 male patients with OSA revealed both positive (e.g., changed something at work or home to get me to use CPAP) and negative (e.g., tried to make me scared of the consequences of not using CPAP) involvement of wives approximately one to two times during the first week of treatment. 43 Frequency of perceived spousal involvement remained the same at 3-mo follow-up except for negative involvement, which had decreased. Perceived collaborative spousal involvement was associated with greater CPAP adherence at 3 mo.…”
Section: Partner Involvementmentioning
confidence: 84%
“…Limited studies suggest partner involvement that is collaborative and supportive is an important facilitator of CPAP use. [42][43][44] Other than two qualitative studies, 13,46 assessment of partner involvement has primarily been from the patients' perspective. Future research needs to take into consideration the dyadic nature of partner involvement and measure spousal involvement independently in both patients and partners as actual and perceived FS Luyster.…”
Section: Co Nclusi O Ns a Nd D I R Ecti O Ns Fo R Future R Ese A Rchmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that increasing helpful spousal involvement may be helpful for both men and women. We previously reported that collaborative involvement and support were associated with higher adherence (Baron et al 2011(Baron et al , 2012. To date only one intervention has specifically involved spouses (Hoy et al 1999) and found that increasing helpful involvement was one part of a successful intervention.…”
Section: Discussionmentioning
confidence: 99%